Multiple fishways mostly maintain upstream teleost movement in a south-eastern Australian river - Rourke, Meaghan L.; Robinson, Wayne; Baumgartner, Lee J.; Doyle, Jonathon; Mallen-Cooper, Martin; Thiem, Jason D.; Broadhurst, Matt K. (Frontiers in Fish Science, 2025)
River development affects fish connectivity, with intra-river issues exacerbated via sequential barriers. Remediation typically involves installing ‘fishways' to facilitate upstream movements. Here we evaluated species-specific upstream fish-passage efficiencies through three sequential vertical-slot fishways along the Nepean River in Australia via paired entry and exit trapping. Species-specific water velocity preferences associated with fishway entrance were informed by restricting head loss at the entry traps, but not at the exit traps. During 78 paired trap deployments 26,139 fish were caught, comprising 19 species; most of which successfully negotiated the fishways—albeit with considerable inter- and intra-specific variability among fishways. Catches of the most abundant species (38% of total), the amphidromous Gobiomorphus coxii (20–160 mm total length; TL), in the entry and exit traps were negatively and positively affected by water velocity, respectively at the second and third fishways, but not at the first. Catches of other species were also directly or indirectly affected by water velocity, with fewer catadromous Trachystoma petardi (145–460 mm fork length; FL) and Mugil cephalus (35–410 mm FL) recorded in entry than exit traps, implying (1) insufficient water velocity to permit entry and/or (2) confounding effects of the entry-trap design on capture. Conversely, two gudgeons [the potamodromous Philypnodon grandiceps (29–77 mm TL) and Hypseleotris galii (31–49 mm TL)] were caught in significantly greater abundances in the entry than exit traps implying some restriction to their passage and possibly due to deficits in fishway hydraulics and/or a lack of motivation to migrate in these species. The study highlights the value of location-specific monitoring for identifying key factors affecting fishway performance.